An analytical study of 50 women presenting with an adnexal mass - Bhagde, Anand Dipak; Jani, Shashwat Kamal; Patel, Megha Snehal; Shah, Sushma Rakesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of this study was to detect and determine the origin of adnexal mass and to narrow down the diagnosis. Also, to determine the reliability of the bimanual pelvic examination in diagnosing adnexal mass and to determine clinical, radiological and histopathological co-relation of adnexal mass. Adnexal mass lesions are fairly common among women (with a prevalence of 0.17% to 5.9% in asymptomatic women and 7.1% to 12% in symptomatic women) of all age group but very common among reproductive age. Differential diagnosis of adnexal mass is difficult and complex. Recognition of the severity of the problem, appropriate and timely evaluation and treatment with good outcome is the goal. Methods: Prospective, observational study of 50 patients with suspected various adnexal masses were conducted for a period of 1.5yr i.e. from November 2014 to May 2016. All patients underwent pelvic and ultrasonography examination. All patients later underwent surgery. Results were correlated later. Results: The patient ages ranged from 19 to 58 with a mean age of 31.5. Most common site of origin of adnexal masses is the Ovary (Rt. 38% and Lt. 34%) Most common adnexal masses on histopathological diagnosis are mucinous cyst adenoma (20%), Benign and mature cystic teratoma (16% and 6%) and serous cyst adenoma (10%). About 92% patients with adnexal mass presents with abdominal pain as a chief complaint. Conclusions: Although bimanual palpation of the adnexal masses may not allow a very specific diagnosis, clinically useful information can usually be obtained and hence it is particularly useful as a first step in assessment of adnexal masses and as an adjunct to morphological assessment of ovarian lesions. Ultrasonography is an important noninvasive investigation and is helpful in diagnosing most of these cases, but the histopathological examination of specimen obtained from laparotomy of adnexal mass is the gold standard for confirming the diagnosis.